Analysis of Carbon Stock in Seagrass Enhalus acoroides in Benan Island, Lingga Regency - Zulfahmi, Sayid; Siregar, Yusni Ikhwan; Zulkifli, Zulkifli (Journal of Coastal and Ocean Sciences, 2020)
This research was conducted in Benan Island, Katang Bidara Subdistrict, Lingga Regency, Riau Islands Province in February 2020. This study aimed to determine the value of density, biomass and carbon stock in seagrass E. acoroides. The method used in this study is a survey method, where the data collected is considered to represent the waters of Benan Island. The density of seagrass E.acoroides in the study location ranged from 22.67 to 31.22 individuals/m2. E.acoroides seagrass is divided into two parts, namely the top of the substrate or above ground biomass (Agb) and the bottom of the substrate or bellows biomass (Bgb). The average value of biomass seagrass ranged from 1,113.27-4,412.24 g/m2. The highest carbon stock was in the rhizoma section at Station I (2,134.46 gC/m2) and the lowest was in the leaf section at Station II (363.08 gC/ m2). Biomass and carbon stock in the Bgb section is higher than the Agb portion